Fruit Scar Incidence and Its Effect on Guava ‘Kristal’ Fruit Quality (Psidium guajava L.) at Low- and Middle-altitude Orchards in Bogor, Indonesia - Musyarofah, Neni; Susanto, Slamet; Aziz, Sandra Arifin; Suketi, Ketty; Dadang, Dadang (Journal of Tropical Crop Science, 2021)
Information on scar incidence and its effect on fruit quality of ‘Kristal’ guava (Psidium guajava L.) grown on different altitudes is currently limited. The aim of this study was to evaluate the fruit scar incidence and fruit quality of 'Kristal' guava var. grown on low- and middle-altitude orchards. The research was conducted by collecting 50 samples of fruit harvested from each orchard from January to June 2019. Fruit quality evaluation was carried out at Postharvest Laboratory, Department of the Agronomy and Horticulture, IPB University, whereas scarring pest observation was conducted at Insect Biosystematics Laboratory, Department of Plant Protection, IPB University. Our results showed that the low-altitude orchard produced more fruits with medium, high, and very high scar intensity, while the middle-altitude orchard produced more fruits with low and very low scar intensity. Fruit scar was caused by fruit scarring pests, especially thrips and mites. Fruit tissue damage only occurred on the epidermis of fruit pericarps where the tissue turned brownish and thickened. Additionally, there was no expansion of the damage into the pulp. The peel damage did not affect the fruit taste as indicated in the level of total soluble solids (TSS), titratable acidity (TA), TSS/TA ratio, vitamin C, and total flavonoids content. Fruit external quality was varied in response to altitude, where middle-altitude orchard produced a heavier, a bigger and a lower fruit softness than low-altitude ones. Present findings could be the baseline information for determine the best growth site and adjustment of pest control to maintain fruit quality.